Allosteric Recognition of Homomeric and Heteromeric Pairs of Monosaccharides by a Foldamer Capsule. (3rd February 2020) - Mateus, Pedro; Chandramouli, Nagula; Mackereth, Cameron D.; Kauffmann, Brice; Ferrand, Yann; Huc, Ivan
Abstract: The recognition of either homomeric or heteromeric pairs of pentoses in an aromatic oligoamide double helical foldamer capsule was evidenced by circular dichroism (CD), NMR spectroscopy, and X‐ray crystallography. The cavity of the host was predicted to be large enough to accommodate simultaneously two xylose molecules and to form a 1:2 complex (one container, two saccharides). Solution and solid‐state data revealed the selective recognition of the α‐ 4 C1 ‐d ‐xylopyranose tautomer, which is bound at two identical sites in the foldamer cavity. A step further was achieved by sequestering a heteromeric pair of pentoses, that is, one molecule of α‐ 4 C1 ‐d ‐xylopyranose and one molecule of β‐ 1 C4 ‐d ‐arabinopyranose despite the symmetrical nature of the host and despite the similarity of the guests. Subtle induced‐fit and allosteric effects are responsible for the outstanding selectivities observed. Abstract : Zwei Monosaccharide passen in einen Container aus einem aromatischen Doppelhelix‐Foldamer. Die Bindung ist hinsichtlich des Zucker‐Anomers, des Pyranose/Furanose‐Tautomers und der Händigkeit der Helix selektiv und ergibt wohldefinierte homomere oder heteromere Komplexe. Ein heteromerer Komplex von 42 möglichen wird selektiv gebildet.